Characterization of phloroglucinol derivatives and diterpenes in Euphorbia ebracteolata Hayata by utilizing ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry - Can-Jian Wang; Ying-Qiao Jiang; Dong-Hui Liu; Xiao-Hong Yan; Shuang-Cheng MA (Elsevier, 2013)
Euphorbia ebracteolata Hayata (E. ebracteolata) is a Chinese herbal medicine used for the treatment of tumor diseases. An ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLCâQâTOF/MS) based chemical profiling approach was established for the rapid separation and characterization on phloroglucinol derivatives and diterpenes in E. ebracteolata. Three phloroglucinol derivatives and nine diterpenes were identified by exact mass measurement and were further confirmed by Ms2 data. In addition, the chemical profiles of six compounds were acquired by reference standards. Furthermore, the fragmentation rules of phloroglucinol derivatives and diterpenes of E. ebracteolata were analyzed, and each chromatographic peak was classified. Keywords: Phloroglucinol derivatives, Diterpenes, Euphorbia ebracteolata Hayata, UPLC-Q-TOF/MS